2015
DOI: 10.1016/j.cmet.2015.01.001
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Gut Adaptation in the Potent Effects of Multiple Bariatric Surgeries on Obesity and Diabetes

Abstract: Summary Bariatric surgical procedures such as vertical sleeve gastrectomy (VSG) and Roux-en-Y gastric bypass (RYGB) are the most potent treatments available to produce sustained reductions in body weight and improvements in glucose regulation. While traditionally these effects are attributed to mechanical aspects of these procedures such as restriction and malabsorption, a growing body of evidence from mouse models of these procedures points to physiological changes that mediate the potent effects of these sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
138
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 191 publications
(147 citation statements)
references
References 100 publications
4
138
0
5
Order By: Relevance
“…Although treatment with SCFAs is not feasible, as they are very unpalatable and do not reach the distal small and large intestine where they are endogenously produced, prebiotic treatment (nondigestible fibre) effectively increases distal intestinal SCFA production and improves glucose homeostasis in rodents (Cani et al 2006b, Everard et al 2011, which is thought to be mediated through an increase in gut peptide release (Cani et al 2004, 2006b, Everard et al 2011, Neyrinck et al 2012. While some evidence exists for the beneficial effects of fermentable dietary fibre in humans (Archer et al 2004, Cani et al 2006a, Parnell & Reimer 2009), intake of dietary fibre is generally low (Howarth et al 2003), and prebiotic treatment may not readily increase propionate production (Chambers et al 2015). As such, a novel carrier molecule was developed to selectively increase colonic propionate levels.…”
Section: Gut Microbiotamentioning
confidence: 99%
See 3 more Smart Citations
“…Although treatment with SCFAs is not feasible, as they are very unpalatable and do not reach the distal small and large intestine where they are endogenously produced, prebiotic treatment (nondigestible fibre) effectively increases distal intestinal SCFA production and improves glucose homeostasis in rodents (Cani et al 2006b, Everard et al 2011, which is thought to be mediated through an increase in gut peptide release (Cani et al 2004, 2006b, Everard et al 2011, Neyrinck et al 2012. While some evidence exists for the beneficial effects of fermentable dietary fibre in humans (Archer et al 2004, Cani et al 2006a, Parnell & Reimer 2009), intake of dietary fibre is generally low (Howarth et al 2003), and prebiotic treatment may not readily increase propionate production (Chambers et al 2015). As such, a novel carrier molecule was developed to selectively increase colonic propionate levels.…”
Section: Gut Microbiotamentioning
confidence: 99%
“…For example, in the RYGB microbiota transplant study described above, levels of propionate were increased in both the RYGB-treated donor and the recipient mice (Liou et al 2013). Indeed, supplementation with propionate or fermentable fibre is known to reduce appetite and improve glucose tolerance, possibly from inducing distal intestinal gut peptide secretion 230:3 (Everard et al 2011, Lin et al 2012, Chambers et al 2015, Psichas et al 2015b. Ileal propionate activates mucosal FFAR2 to lower hepatic glucose production through a GLP-1-dependent neuronal pathway (Zadeh-Tahmasebi et al 2016), while increased concentrations of SCFA in the large intestine have been shown to increase circulating levels of GLP-1 and PYY and reduce postprandial insulin and glucose levels (Tolhurst et al 2012, Psichas et al 2015b).…”
Section: Gut Microbiotamentioning
confidence: 99%
See 2 more Smart Citations
“…A growing body of research now finds this perspective to be outdated. Ongoing investigations are now beginning to piece together a much more complex picture that involves postsurgical changes leading to adaptations in the gut that are modulated by its own hormonal and nervous systems interacting with gut microbia, bile acids, and nutrient delivery (23).…”
Section: How Does Bariatric Surgery Remit Diabetes?mentioning
confidence: 99%